Analisis Survei Kepuasan Pasien Rawat Inap Dengan Metode Sistem Informasi Manajemen Rumah Sakit (SIMRS) Dalam Upaya Mutu Layanan di Rumah Sakit - Manik, Maggie Juntiven; Saputri, Agnes Ratna (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
This study aims to conduct a literature review related to the analysis of inpatient patient satisfaction surveys using the Hospital Management Information System (SIMRS) method as a tool to improve service quality in hospitals. Patient satisfaction surveys are an important instrument in assessing the quality of services provided by hospitals. Through the implementation of SIMRS, the process of collecting, processing, and analysing survey data can be done more efficiently and accurately, thus providing quick and relevant feedback for management decision-making. The literature reviewed included various studies on SIMRS implementation and its impact on improving service quality, particularly in terms of inpatient satisfaction. The review showed that the use of SIMRS contributed to improvements in various aspects of service, such as responsiveness to patient complaints, management of service time, and transparency of medical information. SIMRS also enables better monitoring and evaluation of service quality indicators, supporting continuous improvement in the hospital. Overall, this literature review concludes that the integration of patient satisfaction surveys with SIMRS is an effective approach to improving quality of care in hospitals. SIMRS implementation can accelerate the quality improvement process, improve operational efficiency, and ultimately significantly improve patient satisfaction.